The Strategies Development for Participation in Curriculum Administration of Mahachulalongkornrajavidyalaya University - Uttaravichien, Nat; Prasertphorn, Vanich (Journal of Graduate MCU KhonKaen Campus, 2019)
The purposes of this research were: 1) to study current situation and the desirable conditions of the strategies development for participation in curriculum administration of Mahachulalongkornrajavidyalaya university, 2) to create the strategies development for participation in curriculum administration of Mahachulalongkornrajavidyalaya university and 3) to confirm and examine development strategies for participation in curriculum administration of Mahachulalongkornrajavidyalaya University. The sample group used in the research included 300 heads of curriculums and teachers in curriculums of Mahachulalongkornrajavidyalaya university. The sample size determined by R.V. Krejcie & D.W. Morgan consisted of 169 samples. The sample group of the participants in this research included at least 1 person of the heads and teacher in curriculums from each curriculum. The research instrument was 5-level rating scale questionnaire with content validity between 0.80 - 1.00 and reliability at 0.879. The statistics used for analyzing data comprised mean, standard deviation, frequency, t - test (Independent Samples) and One-Way ANOVA. The data were analyzed by using a computer program. The research results were found that: 1.The current situation and the desirable conditions of the strategies development for participation in curriculum administration of Mahachulalongkornrajavidyalaya university were found that PNImodified, current situation and the desirable conditions of the strategies development for participation in curriculum administration in overall, were rated at 0.27, it means that the rate of developmental change from the current situation to the desired conditions was at a value of 27 percent, when considered in each aspect, it was found that the participation in decision making, commenting, evaluation, operation, interests allocation and responsibility was rated at 0.34, 0.33, 0.29, 0.23, 0.10 and 0.35 respectively, it means that the rate of developmental change from current situation to the desirable conditions was at a value of 34, 33, 29, 23, 10 and 35 percent respectively. 2.The level of opinions on the strategies development for participation in curriculum administration of Mahachulalongkornrajavidyalaya university of the current situation, in overall, classified by gender, age and current position was not different, while a group of majors in overall, was different with statistical significance at the level of .05 and the level of opinion on the strategies development for participation in curriculum administration of Mahachulalongkornrajavidyalaya university of the desirable conditions in overall, classified by gender, current position and a group of majors was not different, while classified by age was different with statistical significance at the level of .05. 3.The strategies development for participation in curriculum administration of Maha chulalongkornrajavidyalaya university consisted of 6 aspects, including the aspect of decision making, commenting, evaluation, operation, interests allocation and responsibility.